PENGARUH MODEL PEMBELAJARAN INTERAKTIF BERBANTUAN MULTIMEDIA TERHADAP MOTIVASI DAN HASIL BELAJAR KIMIA - Ulviana, Ulviana; Haris, Mukhtar; Hadisaputra, Saprizal (Jurnal Pendidikan Progresif, 2016)
The Effect of Interactive Model with Multimedia towards Motivation and Chemistry Learning Outcomes. The study aimed to know the influence of interactive learning model with multimedia on student learning outcomes and motivations. This research was a quasi-experimental with nonequivalent control group design. The populations were all of class X in SMAN 1 Kuripan at 2016/2016 academic years. Two classes (XF and XB) were selected as the sample by purposive sampling technique. Motivation questionnaire was used to measure the student learning motivation, and multiple choice tests was used to measure student learning outcomes. A t-test was applied to analyze the motivation data. The result showed that t stat (0,13) < ttable (1,68), mean that the interactive learning model with multimedia does not enchanced student’s learning motivation. In contrast, the learning outcomes data showed that t stat (3,99) > ttable (1,68), it is revealed that interactive learning model with multimedia is better than conventional models to student learning outcomes. Keywords: interactive learning, multimedia, learning motivations, learning outcomes, oxidation and reduction reaction DOI: http://dx.doi.org/10.23960/jpp.v6.i2.201601